Social history of the true Orthodox Christians wandering in Russia: capitalism, communism, and apocalypse, 1900-1930 - Kuziner, Igor (Imperial transformations, 2026)
"This book explores the social history of the radical religious community of Old Believer-Wanderers during the period of rapid late imperial, early Soviet and Stalinist modernization. The self-titled True Orthodox Christian believed the 17th-century reforms of the Russian Orthodox Church ushered in the reign of an invisible Antichrist. Rejecting the corrupted world, they advocated extreme asceticism-renouncing property, marriage, and all contact with the state. Yet, despite their apocalyptic ideology, the Wanderers thrived in late imperial and early Soviet society, engaging in capitalism, pioneering agricultural cooperatives, and even participating in Stalinist repression. Focusing on three key figures, the book examines how these seemingly isolated Millenarians adapted to rapid modernization-from imperial capitalism to Soviet revolution and Stalinist terror. Their surprising integration challenges assumptions about radical religious groups, revealing both the adaptability of fringe communities and the unexpected flexibility of modernizing regimes. Through their story, the book offers new insights into the relationship between marginalized beliefs and societal transformation. The book offers a nuanced and realistic model of the social outcasts' existence that recovers their agency and subjectivity from the layers of discursive projections by elite commentators. It is a significant contribution to the history of religion and popular religiosity in the Russian Empire and the early Soviet Union and presents new and rare perspective on Russian modernity. It will be of interest to researchers in the fields of Russian history, Christianity, Orthodoxy and the history of religion"--